The Impact of Behavioral, Demographic, Financial Self-Efficacy, and Investors’ Longevity Preferences on Their Decision-Making - Seyfi, Ghazaleh; Hamidian, Mohsen; Baghani, Ali; Chaharmahali, Shahram (Business, Marketing, and Finance Open, 2026)
Investor decision-making is of exceptional and strategic significance from various perspectives. This issue is not limited to increasing investors’ personal profit but also constitutes the foundation for the overall health of the economic system, as investment decisions directly influence future individual well-being, the ability to retire comfortably, fund children’s education, and achieve life goals. Therefore, understanding this process assists investors in avoiding costly mistakes. Considering this importance, the present study investigates the impact of behavioral, demographic, financial self-efficacy, and investors’ longevity preferences on their decision-making. The present research employed a descriptive-survey design with an ex post facto (causal-comparative) approach. Data collection instruments included the review of theoretical foundations, models, academic documents, scientific-research journals, electronic resources, and relevant websites, along with semi-structured in-depth interviews and standardized questionnaires. The statistical population consisted of all active investors in the Tehran Stock Exchange. Using simple random sampling and Cochran’s formula, a sample of 384 investors was selected. Subsequently, researcher-developed questionnaires were distributed among the sample, and 365 completed questionnaires were returned. During the research process, thirteen hypotheses were formulated and tested using the required statistical analyses. The findings indicate that overconfidence, self-attribution bias, and herding behavior have a significant negative impact on investors’ decision-making. In contrast, control and monitoring of daily financial affairs, control over decision-making and financial planning, control over debt and loans, control over investment and risk management, and mid-term investment management exert a significant positive influence on investors’ decision-making.